PROFIL PROSOSIAL PESERTA DIDIK SMP NEGERI 1 SELAAWI GARUT - Neneng Entang; Euis Eti Rohaeti; Devy Sekar Ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
The purpose of this study was to determine the profile of prosocial abilities of class IX students of SMP Negeri 1 Selaawi Garut. Prosocial behavior is the manifestation of positive behavior that benefits others. Prosocial behavior is manifested in three forms of behavior, including helping, comforting, and sharing. The study was conducted at SMP Negeri 1 Selaawi Garut on 78 class IX students with quantitative approaches and descriptive study methods. Based on the research results obtained (1) the average profile of prosocial skills of class IX students of SMP Negeri 1 Selaawi Garut are in the medium category; (2) Comporting indicators occupy the high category, while honestly and helping indicators are in the medium and low categories.Keywords: Prosocial skills, Middle school students